Auditory contributions to visual anticipation in tennis. (May 2018) - Cañal-Bruland, Rouwen; Müller, Florian; Lach, Björn; Spence, Charles
Abstract: Objectives: It is well-known that visual information is crucial to successful anticipation in tennis. Here, we examine whether the sound of a tennis ball being struck by a racquet would influence anticipatory judgments of the ball's trajectory. Design: Within videos of tennis rallies from the semi-final of the Australian Open 2016 between Djokovic and Federer, the intensity of the sounds produced when the racquet hit the ball were manipulated systematically. Methods: Experienced tennis players anticipated where the ball would land in the opponent's half. Results: The results highlight that the louder the sound of the contact between the racquet and ball, the longer participants predicted the ball's trajectory to be. Conclusions: These findings demonstrate that besides the crucial contribution of vision to anticipation, action-related auditory cues can significantly influence predictions of the outcome of strokes in tennis as well. Highlights: We examined to what degree auditory information influences anticipation in tennis. Players watched videos of tennis rallies and predicted the ball's landing location. The loudness of the sound of ball-racquet-contact was manipulated systematically. The louder the sound, the longer the ball trajectory was estimated to be. Action-related auditory cues therefore influence anticipation of strokes in tennis.